A Study of Pragmatic Stylistic Features of Reading Comprehension Texts in College English Test Band-4: Taking the Texts in December 2021 as an Example - Heting Zhai (Journal of Advanced Research in Education, 2023)
As one important test of English proficiency during college in China, CET-4 has long focused on examining students’ reading ability since it started. To probe a nerve of it, this paper is lighted by the framework of pragmatic stylistics, combining ways of Black’s signposts and Read’s stylistic list. From the perspective of structure, vocabulary, and grammar, the pragmatic stylistic features of reading comprehension texts in CET-4 in December 2021 are thus analyzed. The results show that argumentative essays are structured on the author’s opinion while expository essays are on the knowledge; at the vocabulary level, expository essays prefer to employ more diversely while argumentative essays tend to be more balanced in difficulty; at the grammatical level, these two types of texts both use object and adverbial clauses, and they choose simple present and past simple tenses. Also, their sentences are favored active voice.